Lola at last - Peterson, JC; Austen, Jane, 1775-1817. (2023)
"Move over, Elizabeth Bennet. The most infamous Bennet sister is here to tell her story. Join Lola Barnes, a.k.a. a modern Lydia Bennet, at the beginning of a summer gone truly wrong: where a boat party-turned-fiery-fiasco ends with the ship, Lola's summer plans, and her reputation truly sunk. (The boat was barely on fire, for the record--and all the partygoers were just fine.) Luckily, this disaster of a summer has another thing in store for her: a path of self-discovery she never saw coming. Given an ultimatum--jail time, or spending the summer with the nonprofit Hike Like a Girl--she laces up her hiking boots and takes to the wilderness. Along the way, she'll encounter unexpected friends, a sweet romance, strength she didn't know she had--and herself, Lola, at last. This Pride and Prejudice-inspired tale, a companion to J. C. Peterson's Being Mary Bennet, spins a modern Lydia Bennet's life into a tumultuous and hilarious coming-of-age journey, complete with misadventures, misunderstandings, mayhem, and a romance worthy of Darcy and Elizabeth themselves. "--
Keywords: Man-woman relationships -- Juvenile fiction; First loves -- Juvenile fiction; Young women -- Juvenile fiction; Introspection -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Voluntarism -- Juvenile fiction; Man-woman relationships -- Fiction; Girls -- Fiction; Self-actualization -- Fiction; Coming of age -- Fiction; Voluntarism -- Fiction; Young adult fiction; Romance fiction; Humorous fiction; Bildungsromans